Meeting Summary: Global Vaccine and Immunization Research Forum, 2021. Issue 11 (10th March 2023) - Ford, Andrew; Hwang, Angela; Mo, Annie X.; Baqar, Shahida; Touchette, Nancy; Deal, Carolyn; King, Deborah; Earle, Kristen; Giersing, Birgitte; Dull, Peter; Hall, B. Fenton
Highlights: Global collaboration and decades of vaccine research continue to yield benefits. Such investments and experience enabled a rapid response to COVID-19. Advances made due to COVID-19 should be applied to other vaccines and to emergency preparedness. Abstract: The 2021 Global Vaccine and Immunization Research Forum highlighted the considerable advances and recent progress in research and development for vaccines and immunization, critically reviewed lessons learned from COVID-19 vaccine programs, and looked ahead to opportunities for this decade. For COVID-19, decades of investments in basic and translational research, new technology platforms, and vaccines targeting prototype pathogens enabled a rapid, global response. Unprecedented global coordination and partnership have played an essential role in creating and delivering COVID-19 vaccines. More improvement is needed in product attributes such as deliverability, and in equitable access to vaccines. Developments in other priority areas included: the halting of two human immunodeficiency virus vaccine trials due to lack of efficacy in preventing infection; promising efficacy results in Phase 2 trials of two tuberculosis vaccines; pilot implementation of the most advanced malaria vaccine candidate in three countries; trials of human papillomavirus vaccines given in single-dose regimens; and emergency use listing of a novel, oral poliomyelitis type 2 vaccine. More systematic, proactive approaches are being developed for fostering vaccine uptake and demand, aligning on priorities for investment by the public and private sectors, and accelerating policy making. Participants emphasized that addressing endemic disease is intertwined with emergency preparedness and pandemic response, so that advances in one area create opportunities in the other. In this decade, advances made in response to the COVID-19 pandemic should accelerate availability of vaccines for other diseases, contribute to preparedness for future pandemics, and help to achieve impact and equity under Immunization Agenda 2030.